Praktik Penambahan Biaya Transaksi QRIS: Tinjauan Hukum Ekonomi Syariah - Sagita Auranti; Anggi Irawan; Ahmad Misbakh Zainul Musthofa (IAIN Langsa, 2025)
This study aims to analyze the practice of adding QRIS transaction fees from the perspective of Islamic economic law. The research employs a field study with a qualitative normative-empirical approach. Data were collected through interviews and direct observations at Aini Cake Shop, supported by a literature review on fiqh muamalah and relevant QRIS regulations. The findings reveal that imposing additional QRIS transaction fees without prior agreement potentially violates the principles of justice, transparency, and mutual consent (an-taradin) in Islamic economics. While the use of QRIS is fundamentally permissible, unclear fee practices require restructuring to ensure compliance with Islamic business ethics and the values of justice and fairness.